1968
DOI: 10.1002/pol.1968.150060422
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ziegler‐Natta catalysts. Part III. Effect of the structure of titanium trichloride on the polymerization of propylene

Abstract: In addition to differences among the various modifications of TiCl3 there may be certain structural differences even among α‐TiCl3 samples prepared by differences methods. Electron microscopic examination of two samples has revealed widely different free surfaces, in spite of the fact that both the specific surfaces (measured by adsorption) and the polymerization activities were identical. This might be explained by the finding that the surfaces of the free lateral planes and the quantities of the free edges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1968
1968
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus, low coordinated titanium species with two or three vacant sites can be possibly present at the edges and corners of the crystallites surface and highly coordinated titanium species with one vacant site or no vacant site at all known as the main plane, which forms 95% of the catalyst surface may be considered passive from the point of view of the polymerization process. An examination has been done (Kollar et al, 1968) with a polymerization process microscopically and found that two types of polymerization centers exist in TiCl 3 catalyst and another investigation has (John Boor, 1967) determined the coexistence of two different structures for active centers to account for the formation of both isotactic and atactic polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, low coordinated titanium species with two or three vacant sites can be possibly present at the edges and corners of the crystallites surface and highly coordinated titanium species with one vacant site or no vacant site at all known as the main plane, which forms 95% of the catalyst surface may be considered passive from the point of view of the polymerization process. An examination has been done (Kollar et al, 1968) with a polymerization process microscopically and found that two types of polymerization centers exist in TiCl 3 catalyst and another investigation has (John Boor, 1967) determined the coexistence of two different structures for active centers to account for the formation of both isotactic and atactic polymers.…”
Section: Resultsmentioning
confidence: 99%
“…5 s have been found by Keii et al [197] Other indications that may be inferred from the data reported in this section concern the location of the active sites on the surface of the TiCl 3 crystals, and the kinetic mechanism involved in the polymer chain propagation step. Many authors [151,302,350,355,[361][362][363][364] believe the active sites to be located on the sIde faces of violet TiCl 3 crystallites, on the edges between side faces and basal planes (001), on the corners and on the defects of basal planes (001), even though some [335,365] believe basal planes too may take part in the catalytic process.…”
Section: Concentration and Location Of Catalytic Centres In Heterogenmentioning
confidence: 99%
“…This finding has been confir? '.ed and refined further by the electron microscopic work of Kollar, Guttman, and their coworkers (Guttman and Guillet, 1968;Kollar et al, 1968a).…”
Section: Morphologies Of Catalyst and Polymermentioning
confidence: 99%